STUDY OF THE PHYSICAL AND FUNCTIONAL CONDITION OF MIDDLE- DISTANCE RUNNERS - qizi, Salimova Shahzoda Zayniddin (Research Focus International Scientific Journal, 2026)
This article identifies the dynamics of functional development in high-level middle-distance runners within both control and experimental groups. Particular focus is placed on presenting the data obtained through specialized testing protocols during the research process. The pedagogical results analyze the differences in physical capacity indicators between the groups at the conclusion of the study, followed by the formulation of evidence-based conclusions.